Employment Opportunities through Information Sharing at Pennyville Mixed Income Development - Mokoka, Pulane Zippora (My University, 2011)
Housing is a pressing issue in South Africa, which is faced by many challenges that require government intervention. The goal of this paper is to examine the rationale for mixed income development in Pennyville as a strategy to confront urban poverty through information sharing, and further investigate how this sharing of information could lead to access to employment opportunities. The paper will provide a framework that delineates the levels and pathways through which mixed income development can improve the quality of life for the urban poor through information sharing or social networking. The research uses qualitative methodology to collect in-depth information from various informants. The research has shown that government has intervened in reducing poverty through mixed income development that is implemented under the BNG strategy but it will require more than mixed income development to improve the lives of the urban poor and reduce poverty. Factors like urban design and layout of the neighbourhood can also have an impact in changing the lives of the poor and improving social relations among the poor. A sustainable and integrated neighbourhood can also allow for social interaction among residents of different income levels
MM thesis - P&DM
Keywords: Mixed income development; Housing; Information sharing